2001
DOI: 10.1002/prot.1061
|View full text |Cite
|
Sign up to set email alerts
|

Expression in Pichia pastoris and characterization by circular dichroism and NMR of rhodostomin

Abstract: Rhodostomin (Rho) is a snake venom protein isolated from Calloselasma rhodostoma. Rho is a disintegrin that inhibits platelet aggregation by blocking the binding of fibrinogen to the integrin alpha(IIb)beta3 of platelets. Rho produced in Escherichia coli inhibited platelet aggregation with a K(I) value of 263 nM. Although functional, Rho produced in E. coli is misfolded based on our 2D and 3D NMR studies. In order to correct the folding problem, Rho was expressed in Pichia pastoris. The recombinant Rho express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 24 publications
3
41
0
Order By: Relevance
“…Similar phenomenon was observed in our previous study that analyzed the structure of rhodostomin, which contains six pairs of disulfide bonds. NMR examinations indicated that the E. coli-produced rhodostomin was misfolded despite being capable of inhibiting platelet aggregation (46). In contrast, P. pastoris produced correctly folded rhodostomin with all of six intramolecular disulfide pairings formed, which also exhibited higher activity than that from E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Similar phenomenon was observed in our previous study that analyzed the structure of rhodostomin, which contains six pairs of disulfide bonds. NMR examinations indicated that the E. coli-produced rhodostomin was misfolded despite being capable of inhibiting platelet aggregation (46). In contrast, P. pastoris produced correctly folded rhodostomin with all of six intramolecular disulfide pairings formed, which also exhibited higher activity than that from E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…16,44 Den and Rho expression in P. pastoris was achieved using yeast transfer vector (pPICZa A; Invitrogen) and an expression kit (EasySelect version A; Invitrogen) with minor modifications to the manufacturer's instructions. The structural gene of Den was amplified using a polymerase chain reaction (PCR) with the sense primer:…”
Section: Expression and Purification Of Den And Rho In P Pastorismentioning
confidence: 99%
“…15 It consists of 68 amino acids, which includes 12 residues of cysteine and a PRGDMP sequence at positions [48][49][50][51][52][53]. We previously showed 16 that Rho expressed in Pichia pastoris has the same function and structure as native protein. Rho binds to unstimulated and ADP-stimulated platelets in a saturable manner with the dissociation constants of 76 and 74 nM, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pichia pastoris yeast-based expression system is appropriate for the expression of eukaryotic genes and has been used with great success over the last decade (Cregg et al, 2000;Guo et al, 2001;Fang et al, 2004). As a eukaryote, P. pastoris has many advantages: improved expression of higher eukaryotic proteins due to correct processing, folding, and post-translational modification of the recombinant protein akin to that of the natural protein; retention of antigenic determinants yielding robust immune responses; and the potential for the protein to be secreted directly into liquid medium, which facilitates purification.…”
Section: Introductionmentioning
confidence: 99%